Penerapan Pembelajaran The Power of Two Untuk Meningkatkan Minat pada Mata Pelajaran Matematika - Tri Yuliasyah Bintaro (JSSH (Jurnal Sains Sosial dan Humaniora), 2018)
This research is a type of Classroom Action Research by applying the learning of The Power of Two. The aim of this research is for: 1) Improving the student’s interest in learning by The Power of Two, 2) improve mathematics learning achievement by The Power of Two. This research use Classroom Action Research Methode which apply in to two cycles, which is the activitiesof each cycle consist of plan, action, observation, evaluation and reflection. The subject in this research are the students in 6 grade at MI Al-Ikhlas. This research involve two lecturers, two college students, and a teacher. The instruments ofcreativity research use student interest questionnaires, instrument of mathematics learning achievement research use an integers material description test. The data analysis use qualitative and quantitative descriptive analysis. The result of this research are : 1) The Power of Two as a learning model to improve interest in learning mathematics. This increasing is indicated by the score average of student’s interest in the cycle I amount 2,50 and the cycle II amount 3,08; 2) learning model The Power of Two can improve mathematics learning achievement. It is indicated by evaluation result in the cycle I gainedan average of 54, 17 with classical provisions 33,33% and the result increase in the cycle II the average amount 73,04 and classical provisions 84,6%.